2020-21 Influenza vaccination campaign strategy as a model for the third COVID-19 vaccine dose? - Lecce, Maurizio; Perrone, Pier Mario; Bonalumi, Federica; Castaldi, Silvana; Cremonesi, Monica (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Seasonal influenza exerts a deep and multi-level impact on population and public health systems. Among at risk groups, healthcare workers (HCWs) represent a crucial one due to the threat of absenteeism and consequent disruption of healthcare services (and economic losses). Also in this group vaccine hesitancy is a well known issue, therefore innovative and 360-degree strategies are urgently needed to overcome the problem. Methods: in the 2020-21 influenza vaccination campaign in a research and teaching hospital in Milan, Italy, the working group implemented three different strategies: the offer of vaccination through both an ad hoc ambulatory and several itinerant (on site) vaccinating teams, a promotional and educational communication campaign, a gaming strategy Results: vaccinated employees nearly doubled (2103 vs 1153 in 2019-20 flu vaccination campaign), reaching a comprehensive vaccination coverage rate (VCR) of 43,1%. A highly significant increase in the 40-59 age group was registered. While physicians and nursing staff confirmed to be the most represented categories among vaccinated subjects, administrative and auxiliary staffs performed the greatest increase compared to the previous campaign. The on site vaccination was clearly preferred than the ad hoc one (1693 HCWs, 80,5% vs 410, 19,5%). Vaccinated for the first time registered a significant increase (40,2% vs 36,2% in 2019-20 campaign). Conclusions: such meaningful results confirm the effectiveness of the strategies implemented in the present campaign, suggesting their possible application in the debated COVID19-third-dose vaccination campaign.